Feasibility study of solar powered bicycle race - Mohd Hafifi, Sabri (2010)
There are many solar race in this era such as solar bicycle race, solar car race and other. Because of solar race regulations system which have similarities in using battery as storage power, the idea to customize the system solar race especially solar bicycle race come to mind. This study purpose is to develop guideline for solar powered bicycle race and prove the feasibility with simulation. So, this study is based on choosing the suitable components and the relations between them. With the suitable selection of the components in this study, guideline has been developed as the strategy to win the race. This study will use fully solar powered as energy to move the bicycle. The result of this study will produce a bicycle that can finish the race in below 19 second in 100 meter. This thesis can be use as a reference and guideline to other people or organization to organize a solar bicycle race competition